An Investigation into Metonymy Denoting “Woman” in English and Vietnamese Songs - Nguyễn Thị Thùy Trâm (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study investigates into the syntactic and semantic features of metonymic expressions in English and Vietnamese songs. This descriptive study focuses on finding the diversity of metonymic expressions in both languages. Under the framework of cognitive linguistics, we looked into how Enlgish and Vietnamese metonymic expressions were used in reference to the idealized conceptual models and principle of cognitive salience. We found that English and Vietnamese share several conceptual models in metonymic mapping concerning the use of metonymic expressions in different songs. Basing on these findings, implications about syntactic and semantic features of metonymic expressions in English and Vietnamese have been proposed to the Vietnamese learners of English for effective language transfer in interpreting and using metonymy.